Alcohol-peelable optical adhesive sheet
By using photopolymers as the matrix and performing ethanol release and high temperature and high humidity testing, the adhesion strength and repeatability of optical pressure-sensitive films are optimized, and the problem of low adhesion strength of existing films in high humidity environments is solved, and the adhesion reliability and reprocessability are improved.
Patent Information
- Application Number
- JP2023158337
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-04
AI Technical Summary
Existing optical pressure-sensitive films have low adhesion strength in high humidity environments and cannot provide good adhesion reliability and reprocessability.
Photopolymers are used as matrix polymers and the film adhesion strength and repeatability are optimized by ethanol release test and high temperature and high humidity peel test.
It achieves a high adhesion strength in a high humidity environment, while also having good ethanol release performance and long-term reprocessing.
Smart Images

Figure 2025049868000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical pressure-sensitive adhesive sheet. [Background technology]
[0002] A display panel has a laminated structure including elements such as a pixel panel, a polarizing film, and a cover film. In the manufacturing process of a display panel, for example, an optically transparent adhesive sheet (optical adhesive sheet) is used to bond the elements included in the laminated structure.
[0003] On the other hand, optical adhesive sheets having water peelability are known. A water peelable optical adhesive sheet is an optical adhesive sheet that can reduce the adhesive strength by infiltrating water droplets into the interface between the adherend and the adhesive sheet after being attached to the adherend. After being attached to the adherend, such an optical adhesive sheet can be easily peeled off from the adherend using water as necessary. For example, in the manufacturing process of a display panel, if a defect (such as misalignment) occurs in the attachment of an optical adhesive sheet to an adherend, the adhesive sheet can be peeled off from the adherend using water (water peelability), and a lamination operation can be performed with a replacement optical adhesive sheet. Such an optical adhesive sheet having water peelability is described, for example, in Patent Document 1 below. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-23679 A Summary of the Invention [Problem to be solved by the invention]
[0005] The optical adhesive sheet described in Patent Document 1 contains an acrylic-based polymer and a surfactant. In this adhesive sheet, the acrylic-based polymer ensures adhesion to the adherend. In addition, in this adhesive sheet, the presence of a surfactant on the adhesive surface results in water peelability. However, the optical adhesive sheet of Patent Document 1 has low moisture resistance due to the presence of a surfactant on the adhesive surface. For example, the optical adhesive sheet of Patent Document 1 has low adhesive strength in a high humidity environment. Such an optical adhesive sheet does not provide good adhesion reliability to the adherend.
[0006] The present invention provides an alcohol-peelable optical pressure-sensitive adhesive sheet that is suitable for achieving both adhesive reliability to an adherend and reworkability. [Means for solving the problem]
[0007] The present invention [1] contains a photopolymerized polymer as a base polymer, and has an initial adhesive strength Fn in the following room temperature peel test. 1 The adhesive strength in the first ethanol peeling test below is Fa 1 This includes alcohol-peelable optical adhesive sheets having an adhesive strength Fh of 3.0 N / 25 mm or less and an adhesive strength Fh of 2.0 N / 25 mm or more in the high-temperature, high-humidity peel test described below.
[0008] Initial cold peel test: First, a 25 mm wide x 100 mm long adhesive sheet piece of the alcohol-peelable optical adhesive sheet is attached to an alkali glass plate prepared by the float method to obtain a laminate (preparation step). Next, the laminate is heated and pressurized at 50°C, 0.5 MPa, and 15 minutes (heating and pressurizing step). Next, the laminate is left to stand at room temperature for 72 hours (standing step). Next, the adhesive sheet piece is peeled off from the alkali glass plate by pulling one end of the adhesive sheet piece in the length direction under first conditions of 25°C, relative humidity of 50%, peeling angle of 180°, and pulling speed of 300 mm / min, to measure the adhesive strength (measurement step).
[0009] First ethanol stripping test: The procedure is the same as the initial room temperature peel test, except for the following: In the standing step, the laminate is stood at 50°C for 168 hours; After the standing step and before the measurement step, an ethanol supplying step is carried out; In the ethanol supplying step, 10 μL of ethanol is supplied onto the alkali glass plate of the laminate so that the ethanol contacts one end of the adhesive sheet piece in the longitudinal direction at the interface between the alkali glass plate and the adhesive sheet piece.
[0010] High temperature and high humidity peel test: The procedure is the same as the initial room temperature peel test, except for the following: In the standing step, the laminate is stood at room temperature for 24 hours; After the standing step and before the measurement step, a high temperature and humidity treatment step is carried out; In the high temperature and humidity treatment step, the laminate after the standing step is subjected to high temperature and humidity treatment under conditions of 60°C, relative humidity of 93%, and 15 minutes; In the measurement step, a 180° peel test is carried out under second conditions of 60°C, relative humidity of 93%, a peel angle of 180°, and a tensile speed of 300 mm / min, instead of the first conditions.
[0011] The present invention [2] has an adhesive strength Fa in the second ethanol peeling test described below. 2 The adhesive strength Fa 2 The adhesive force Fa 1 The alcohol-peelable optical adhesive sheet according to the above item [1] includes the alcohol-peelable optical adhesive sheet according to the above item [1], wherein the fluctuation rate of
[0012] Second Ethanol Strip Test: The test was the same as the first ethanol peeling test, except that in the standing step, the laminate was stood at room temperature for 72 hours.
[0013] The present invention [3] includes the alcohol-peelable optical adhesive sheet according to the above [1] or [2], which has an ethanol peeling duration of 20 mm or more in the second ethanol peeling test.
[0014] The present invention [4] includes an alcohol-peelable optical adhesive sheet according to any one of the above [1] to [3], which does not contain a surfactant. Effect of the Invention
[0015] As described above, the alcohol-peelable optical adhesive sheet of the present invention has a base polymer that is a photopolymerized polymer, and an initial adhesive strength Fn 1 The adhesive strength in the first ethanol peel test is 9.0N / 25mm or more. 1 The adhesive strength Fn is 3.0N / 25mm or less, and the adhesive strength Fh in the high temperature and high humidity peel test is 2.0N / 25mm or more. 1 A high adhesive strength of 9.0 N / 25 mm or more (when ethanol is not supplied) is suitable for ensuring the adhesive reliability of the alcohol-peelable optical adhesive sheet to the adherend after the sheet is attached to the adherend. 1 A low adhesive strength of 3.0 N / 25 mm or less (adhesive strength under ethanol supply conditions after storage) is suitable for ensuring reworkability by allowing the alcohol-peelable optical adhesive sheet to exhibit good alcohol peelability over a long period of time after it is attached to an adherend. A high adhesive strength Fh (adhesive strength under conditions of no ethanol supply and high temperature and humidity) of 2.0 N / 25 mm or more is suitable for ensuring the adhesion reliability of the optical adhesive sheet to the adherend even in a high humidity environment. Therefore, the alcohol-peelable optical adhesive sheet of the present invention is suitable for achieving both adhesion reliability to the adherend and reworkability. [Brief description of the drawings]
[0016] [Figure 1] 1 is a schematic cross-sectional view of an alcohol-peelable optical adhesive sheet according to one embodiment of the present invention. [Diagram 2] 1 is a schematic diagram showing an ethanol peeling test. [Diagram 3] 1 shows an example of a peel force-peel length curve obtained in an ethanol peel test. [Figure 4]This shows an example of a method of using the alcohol-peelable optical adhesive sheet shown in Fig. 1. Fig. 4A shows a step of attaching the alcohol-peelable optical adhesive sheet to a first adherend, Fig. 4B shows a step of joining the first adherend and the second adherend via the alcohol-peelable optical adhesive sheet, and Fig. 4C shows an aging step. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] As shown in Fig. 1, an adhesive sheet 10 as one embodiment of the alcohol-peelable optical adhesive sheet of the present invention has a sheet shape of a predetermined thickness and extends in a direction (plane direction) perpendicular to the thickness direction H. The adhesive sheet 10 has an adhesive surface 11 and an adhesive surface 12 opposite to the adhesive surface 11. Fig. 1 exemplarily shows a state in which release liners L1, L2 are bonded to the adhesive surfaces 11, 12 of the adhesive sheet 10. The release liner L1 is disposed on the adhesive surface 11. The release liner L2 is disposed on the adhesive surface 12.
[0018] The adhesive sheet 10 is an optically transparent adhesive sheet (optical adhesive sheet). The adhesive sheet 10 is an optical adhesive sheet having alcohol releasability. That is, the adhesive sheet 10 is an optical adhesive sheet whose adhesive strength can be reduced by infiltrating alcohol (e.g., alcohol droplets) into the interface between the adherend and the adhesive sheet 10 after it is attached to the adherend (alcohol releasability).
[0019] The adhesive sheet 10 is a sheet-like pressure-sensitive adhesive. The adhesive sheet 10 contains a photopolymerized polymer as a base polymer. Specifically, the base polymer is a polymerized product obtained by photopolymerization of a polymerizable component such as a monomer component. Photopolymerization is a polymerization method in which a polymerization reaction of a polymerizable component is advanced by irradiation with active energy rays such as ultraviolet light. The adhesive sheet 10 also has an adhesive strength Fn 1 The adhesive strength in the first ethanol peeling test below is Fa 1The adhesive strength Fh in the high temperature and high humidity peel test described below is 2.0 N / 25 mm or more.
[0020] Initial cold peel test: First, a 25 mm wide x 100 mm long adhesive sheet piece of the adhesive sheet 10 is attached to an alkali glass plate prepared by the float method to obtain a laminate (preparation step). In this step, the adhesive sheet piece is attached to the tin surface of the alkali glass plate (the same applies to other peel tests described later). Next, the laminate is heated and pressurized under conditions of 50°C, 0.5 MPa, and 15 minutes (heating and pressurizing step). Next, the laminate is left to stand at room temperature for 72 hours (standing step). Next, the adhesive sheet piece is peeled off from the alkali glass plate by pulling one end of the adhesive sheet piece in the length direction under first conditions of 25°C, relative humidity 50%, peel angle 180°, and pulling speed 300 mm / min, to measure the adhesive strength (measurement step). The method of the initial room temperature peel test is more specifically as described below in the examples.
[0021] First ethanol stripping test: The test is the same as the initial room temperature peel test except for the following. In the standing step, the laminate is left standing at 50°C for 168 hours. After the standing step and before the measurement step, an ethanol supplying step is performed. In the ethanol supplying step, 10 μL of ethanol (100% ethanol) is supplied onto the alkali glass plate of the laminate so that the ethanol contacts one end of the adhesive sheet piece in the length direction at the interface between the alkali glass plate and the adhesive sheet piece. Specifically, as shown in FIG. 2, 10 μL of ethanol 22 is supplied onto the alkali glass plate 21 of the laminate W so that the ethanol 22 contacts one end 10a in the length direction D of the adhesive sheet piece 10A at the interface B between the alkali glass plate 21 and the adhesive sheet piece 10A. In the measurement step after the ethanol supplying step, the adhesive sheet piece 10A is peeled off from the alkali glass plate by pulling one end side in the length direction of the adhesive sheet piece 10A (one end 10e in FIG. 2) to measure the adhesive strength. The method of the first ethanol peel test is described more specifically below with reference to the examples.
[0022] Fig. 3 shows an example of a peel force-peel length curve obtained in an ethanol peel test (first ethanol peel test, second ethanol peel test described below). In the graph of Fig. 3, the horizontal axis represents the peel length (mm) from the start of peeling of the adhesive sheet piece in the measurement step (peel length 0 mm), and the vertical axis represents the peel force (N / 25 mm) required to peel the adhesive sheet piece during the peeling process. In the measurement step of the ethanol peel test, the peel length d 1 and peel length d 1 When the peeling force increases by 10% from the peeling force at 2 (If the peel force does not increase by 10%, the peel length d 2 is the length of the adhesive sheet piece 100mm-d 1 ) and the peel length d 1 From peel length d 2 The average peel strength measured up to the end of the experiment was used as the adhesive strength (adhesive strength in the ethanol peel test, Fa 1 ,Fa 2 )
[0023] High temperature and high humidity peel test: The procedure is the same as the initial room temperature peel test, except for the following: In the resting step, the laminate is left at room temperature for 24 hours; After the resting step and before the measurement step, a high temperature and humidity treatment step is performed; In the high temperature and humidity treatment step, the laminate after the resting step is subjected to high temperature and humidity treatment under conditions of 60°C, relative humidity 93%, and 15 minutes; In the measurement step, instead of the first condition, a 180° peel test is performed under second conditions of 60°C, relative humidity 93%, a peel angle of 180°, and a tensile speed of 300 mm / min. More specifically, the method of the high temperature and humidity peel test is as described below in relation to the examples.
[0024] As described above, the adhesive sheet 10 has a base polymer that is a photopolymerized polymer, and an initial adhesive strength Fn 1 The adhesive strength in the first ethanol peel test is 9.0N / 25mm or more. 1The adhesive strength Fn is 3.0N / 25mm or less, and the adhesive strength Fh in the high temperature and high humidity peel test is 2.0N / 25mm or more. 1 A high adhesive strength of 9.0 N / 25 mm or more (under the condition where ethanol is not supplied) is suitable for ensuring the adhesive reliability of the adhesive sheet 10 to the adherend after the adhesive sheet 10 is attached to the adherend. 1 A low adhesive strength of 3.0 N / 25 mm or less (adhesive strength after storage under ethanol supply conditions) is suitable for ensuring reworkability by allowing the adhesive sheet 10 to exhibit good alcohol peelability for a long period of time after the adhesive sheet 10 is attached to an adherend (long-term reworkability). A high adhesive strength Fh (adhesive strength under conditions of no ethanol supply and high temperature and humidity) of 2.0 N / 25 mm or more is suitable for ensuring the adhesive reliability of the adhesive sheet 10 to the adherend even in a high humidity environment. Thus, the adhesive sheet 10 is suitable for achieving both adhesive reliability to the adherend and reworkability (alcohol reworkability).
[0025] In addition, unlike the water peelability of the optical adhesive sheet of Patent Document 1, which is expressed depending on a surfactant, the present inventors have found that the optical adhesive sheet can exhibit alcohol peelability over a relatively long period of time without relying on a surfactant. The present invention is based on such findings. Not relying on a surfactant is suitable for ensuring the adhesion reliability of the optical adhesive sheet to the adherend even in a high humidity environment.
[0026] Adhesive force Fn 1 From the viewpoint of ensuring the above-mentioned bonding reliability, the adhesive strength Fn is preferably 9.5 N / 25 mm or more, and more preferably 10 N / 25 mm or more. 1 From the viewpoint of ensuring the reworkability, the adhesive strength Fn is preferably 19 N / 25 mm or less, more preferably 18 N / 25 mm or less, and even more preferably 17 N / 25 mm or less. 1 From the viewpoint of achieving both bonding reliability and reworkability, the adhesive strength Fn is preferably 9.0 to 19 N / 25 mm, more preferably 9.5 to 18 N / 25 mm, and even more preferably 10 to 17 N / 25 mm. 1Examples of methods for adjusting the adhesive strength Fn include selecting the type of base polymer in the adhesive sheet 10, adjusting the molecular weight, adjusting the degree of crosslinking, and adjusting the blending amount. Examples of methods for these adjustments include selecting the type and adjusting the blending amount of monofunctional monomers, polyfunctional polymerizable compounds (crosslinking agents), and polymerization initiators when forming the base polymer. 1 The adjustment method of adhesive strength Fa can be selected by selecting the type of components other than the base polymer in the adhesive sheet 10 and adjusting the amount of the components. Examples of the components include oligomers (hydrophilic oligomers, hydrophobic oligomers), surfactants, and silane coupling agents. 1 , Fh and adhesive strength Fn 2 ,Fa 2 The same applies to.
[0027] Adhesive strength Fa 1 From the viewpoint of ensuring the alcohol reworkability of the pressure-sensitive adhesive sheet 10, the adhesive strength Fa is preferably 2.7 N / 25 mm or less, more preferably 2.4 N / 25 mm or less, and even more preferably 2.0 N / 25 mm or less. 1 From the viewpoint of preventing unintended peeling of the adhesive sheet 10 when an alcohol-containing liquid (such as a disinfectant) is applied to the adhesive sheet 10, the adhesive strength Fa is preferably 0.5 N / 25 mm or more, more preferably 0.8 N / 25 mm or more, even more preferably 1.0 N / 25 mm or more, and even more preferably 1.2 N / 25 mm or more. 1 From the viewpoint of achieving both the alcohol reworkability of the pressure-sensitive adhesive sheet 10 and the suppression of the unintended peeling, the adhesive strength is preferably 0.5 to 3.0 N / 25 mm, more preferably 0.8 to 2.7 N / 25 mm, even more preferably 1.0 to 2.4 N / 25 mm, and even more preferably 1.2 to 2.0 N / 25 mm.
[0028] The adhesive strength Fh is preferably 2.1 N / 25 mm or more, more preferably 2.2 N / 25 mm or more, from the viewpoint of ensuring the bonding reliability of the adhesive sheet 10 in a high humidity environment. The adhesive strength Fh is preferably 10 N / 25 mm or less, more preferably 7.0 N / 25 mm or less, and even more preferably 5.0 N / 25 mm or less, from the viewpoint of ensuring reworkability. Adhesive strength Fn 1 From the viewpoint of achieving both the bonding reliability and reworkability of the pressure-sensitive adhesive sheet 10 in a high-humidity environment, the adhesive strength is preferably 2.0 to 10 N / 25 mm, more preferably 2.1 to 7.0 N / 25 mm, and even more preferably 2.2 to 5.0 N / 25 mm.
[0029] The adhesive sheet 10 had an adhesive strength Fn 2 has.
[0030] Peel test at room temperature after storage: The procedure was the same as that of the initial room temperature peel test, except that in the resting step, the laminate was left to stand for 168 hours at 50° C. The method for the room temperature peel test after storage was specifically as described later in the Examples.
[0031] Adhesive force Fn 2 From the viewpoint of ensuring long-term bonding reliability of the adhesive sheet 10, the adhesive strength Fn is preferably 9.0 N / 25 mm or more, more preferably 9.5 N / 25 mm or more, and even more preferably 10 N / 25 mm or more. 2 From the viewpoint of ensuring the reworkability, the adhesive strength Fn is preferably 19 N / 25 mm or less, more preferably 18 N / 25 mm or less, and even more preferably 17 N / 25 mm or less. 2 From the viewpoint of achieving both long-term bonding reliability and reworkability, the bonding strength is preferably 9.0 to 19 N / 25 mm, more preferably 9.5 to 18 N / 25 mm, and further preferably 10 to 17 N / 25 mm.
[0032] The adhesive sheet 10 had an adhesive strength of Fa 2 has.
[0033] Second Ethanol Strip Test: The method of the second ethanol peeling test is the same as that of the first ethanol peeling test, except that in the standing step, the laminate is stood at room temperature for 72 hours. The method of the second ethanol peeling test is specifically as described later in the examples.
[0034] Adhesive strength Fa 2 Adhesion strength to Fa 1 From the viewpoint of ensuring stable alcohol reworkability of pressure-sensitive adhesive sheet 10, the rate of change represented by the following formula is preferably −50% to 100%, more preferably −20% to 70%, and even more preferably 0% to 60%.
[0035] Fluctuation rate (%) = [(Fa 1 -Fa 2 ) / Fa 2 ] x 100
[0036] Adhesive strength Fa 2 From the viewpoint of ensuring the alcohol reworkability of the pressure-sensitive adhesive sheet 10, the adhesive strength Fa is preferably 2.5 N / 25 mm or less, more preferably 2.0 N / 25 mm or less, and even more preferably 1.8 N / 25 mm or less. 2 From the viewpoint of preventing unintended peeling of the adhesive sheet 10 when the alcohol-containing liquid is applied to the adhesive sheet 10, the adhesive strength Fa is preferably 0.5 N / 25 mm or more, more preferably 0.8 N / 25 mm or more, and even more preferably 1.0 N / 25 mm or more. 2 From the viewpoint of achieving both alcohol reworkability in pressure-sensitive adhesive sheet 10 and suppression of the above-mentioned unintended peeling, the adhesive strength is preferably 0.5 to 2.5 N / 25 mm, more preferably 0.8 to 2.0 N / 25 mm, and even more preferably 1.0 to 1.8 N / 25 mm.
[0037] The ethanol peeling duration d in the second ethanol peeling test is preferably 20 mm or more, more preferably 26 mm or more, and even more preferably 28 mm or more, from the viewpoint of ensuring the alcohol reworkability of the pressure-sensitive adhesive sheet 10. The ethanol peeling duration d is, for example, 100 mm or less. The ethanol peeling duration d is the above-mentioned peeling length d 2 and peel length d 1 Difference from (d2 -d 1 The method for measuring the ethanol peeling duration d is specifically as described later in the Examples.
[0038] The adhesive sheet 10 is a sheet-like pressure-sensitive adhesive formed from an adhesive composition. The adhesive sheet 10 (adhesive composition) contains at least the above-mentioned photopolymerized polymer as a base polymer.
[0039] Examples of the base polymer include acrylic polymer, polyurethane polymer, polyamide polymer, and polyvinyl ether polymer. The base polymer may be used alone or in combination of two or more. From the viewpoint of ensuring good adhesion and transparency in the adhesive sheet 10, the base polymer is preferably an acrylic polymer. The acrylic polymer is a copolymer of monomer components containing 50% or more by mass of (meth)acrylic acid ester. "(Meth)acrylic" means acrylic and / or methacrylic.
[0040] In this embodiment, the acrylic polymer is a polymer (photopolymerized polymer) obtained by photopolymerization of a polymerizable component including a monofunctional monomer and a polyfunctional polymerizable compound as a crosslinking agent. The acrylic polymer is, for example, a polymer obtained by photopolymerization of a partial polymer (a mixture of a polymer of a monofunctional monomer and an unreacted monofunctional monomer) obtained by photopolymerization of a monofunctional monomer and a polyfunctional polymerizable compound.
[0041] Such an acrylic polymer includes a photopolymerized polymer (first photopolymerized polymer) having a photocrosslinked structure. The photocrosslinked structure is a structure in which a linear structure of units derived from a monofunctional monomer is crosslinked by a unit derived from a crosslinking agent. The base polymer may include a photopolymerized polymer (second photopolymerized polymer) that does not have such a photocrosslinked structure. The second photopolymerized polymer is a polymer of a monofunctional monomer.
[0042] The monofunctional monomer preferably contains a monofunctional (meth)acrylic acid alkyl ester, and more preferably contains a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 20 carbon atoms. The (meth)acrylic acid alkyl ester may have a linear or branched alkyl group, or may have a cyclic alkyl group (alicyclic alkyl group).
[0043] Examples of (meth)acrylic acid alkyl esters having a linear or branched alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, Examples of such acrylates include nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (i.e., (meth)acrylic laurate), isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, cetyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, and nonadecyl (meth)acrylate.
[0044] Examples of the (meth)acrylic acid alkyl ester having an alicyclic alkyl group include (meth)acrylic acid cycloalkyl ester, (meth)acrylic acid alkyl ester having a bicyclic aliphatic hydrocarbon ring, and (meth)acrylic acid alkyl ester having a tricyclic or higher aliphatic hydrocarbon ring. Examples of the (meth)acrylic acid cycloalkyl ester include (meth)acrylic acid cyclopentyl, (meth)acrylic acid cyclohexyl, (meth)acrylic acid cycloheptyl, and (meth)acrylic acid cyclooctyl. Examples of the (meth)acrylic acid alkyl ester having a bicyclic aliphatic hydrocarbon ring include (meth)acrylic acid isobornyl. Examples of (meth)acrylic acid alkyl esters having three or more aliphatic hydrocarbon rings include dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate.
[0045] The monofunctional (meth)acrylic acid alkyl ester may be used alone or in combination of two or more kinds. The monofunctional (meth)acrylic acid alkyl ester is preferably an acrylic acid alkyl ester having an alkyl group having 6 to 12 carbon atoms, and more preferably at least one selected from the group consisting of 2-ethylhexyl acrylate (2EHA) and acrylic laurate (LA).
[0046] The ratio of the (meth)acrylic acid alkyl ester in the monofunctional monomer is preferably 70 to 99.9% by mass, more preferably 80 to 99.5% by mass, and even more preferably 90 to 99% by mass. The ratio of the (meth)acrylic acid alkyl ester in the monofunctional monomer is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. When the ratio of the (meth)acrylic acid alkyl ester is equal to or more than the lower limit, the adhesive sheet 10 can appropriately exhibit basic properties such as adhesiveness. In addition, the ratio of the monofunctional (meth)acrylic acid alkyl ester in the monofunctional monomer is, for example, 99.9% by mass or less, 99.5% by mass or less, or 99% by mass or less.
[0047] The monofunctional monomer may include a copolymerizable monomer that is copolymerizable with the (meth)acrylic acid alkyl ester. Examples of the copolymerizable monomer include a polar group-containing monomer. Examples of the polar group-containing monomer include a hydroxyl group-containing monomer, a monomer having a nitrogen atom-containing ring, and a carboxyl group-containing monomer. The copolymerizable monomer may be used alone or in combination of two or more kinds. The polar group-containing monomer is useful for modifying the acrylic polymer, such as ensuring the cohesive force of the acrylic polymer. The polar group-containing monomer is preferably at least one selected from the group consisting of a hydroxyl group-containing monomer and a monomer having a nitrogen atom-containing ring.
[0048] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. The hydroxyl group-containing monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl acrylate (2HEA), 4-hydroxyethyl acrylate (4HEA), and 4-hydroxybutyl acrylate (4HBA).
[0049] The ratio of the hydroxyl group-containing monomer in the monofunctional monomer is preferably 0.1 to 20% by mass, more preferably 0.5 to 15% by mass, and even more preferably 1 to 12% by mass. The ratio of the hydroxyl group-containing monomer in the monofunctional monomer is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more. When the ratio of the hydroxyl group-containing monomer is equal to or more than the above lower limit, the cohesive force of the pressure-sensitive adhesive sheet 10 can be ensured, and the adhesive force of the pressure-sensitive adhesive sheet 10 to the adherend can be ensured. In addition, the ratio of the hydroxyl group-containing monomer in the monomer component is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 12% by mass or less. When the ratio of the hydroxyl group-containing monomer is equal to or less than the above upper limit, the polarity of the acrylic polymer (related to the compatibility of the acrylic polymer with various additive components in the pressure-sensitive adhesive sheet 10) can be appropriately adjusted.
[0050] Examples of monomers having a nitrogen atom-containing ring include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, and acryloylmorpholine. The monomer having a nitrogen atom-containing ring is preferably N-vinyl-2-pyrrolidone (NVP).
[0051] The ratio of the monomer having a nitrogen atom-containing ring in the monofunctional monomer is preferably 0.1 to 20% by mass, more preferably 0.5 to 12% by mass, and even more preferably 1 to 8% by mass. The ratio of the monomer having a nitrogen atom-containing ring in the monofunctional monomer is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more. When the ratio of the monomer having a nitrogen atom-containing ring is equal to or more than the above lower limit, the cohesive force of the pressure-sensitive adhesive sheet 10 can be ensured, and the adhesive force of the pressure-sensitive adhesive sheet 10 to the adherend can be ensured. Furthermore, the ratio of the monomer having a nitrogen atom-containing ring in the monofunctional monomer is preferably 20% by mass or less, more preferably 12% by mass or less, and even more preferably 8% by mass or less. When the ratio of the monomer having a nitrogen atom-containing ring is equal to or less than the above upper limit, the glass transition temperature of the acrylic polymer can be appropriately adjusted, and the polarity of the acrylic polymer (related to the compatibility of various additive components in the pressure-sensitive adhesive sheet with the acrylic polymer) can be appropriately adjusted.
[0052] Examples of carboxy group-containing monomers include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.
[0053] The ratio of the carboxyl group-containing monomer in the monofunctional monomer is preferably 0.0 to 3 mass%, more preferably 0.0 to 1 mass%, even more preferably 0.0 to 0.5 mass%, and even more preferably 0.0 to 0.1 mass%. The ratio of the carboxyl group-containing monomer in the monofunctional monomer is preferably 3 mass% or less, more preferably 1 mass% or less, even more preferably 0.5 mass% or less, even more preferably 0.1 mass% or less, and particularly preferably 0.0 mass%. When the ratio of the carboxyl group-containing monomer in the monofunctional monomer is the above upper limit or less, corrosion by acid can be suppressed in the adherend of the pressure-sensitive adhesive sheet 10.
[0054] The monofunctional monomer may contain other copolymerizable monomers, such as acid anhydride monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, epoxy group-containing monomers, cyano group-containing monomers, alkoxy group-containing monomers, and aromatic vinyl compounds.
[0055] Examples of the polyfunctional polymerizable compound include polyfunctional monomers containing two or more ethylenically unsaturated double bonds in one molecule. Examples of the polyfunctional monomer include polyfunctional (meth)acrylates. Examples of the polyfunctional (meth)acrylates include bifunctional (meth)acrylates, trifunctional (meth)acrylates, and tetrafunctional or higher polyfunctional (meth)acrylates.
[0056] Examples of bifunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol dimethacrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, glycerin di(meth)acrylate, neopentyl glycol di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, dicyclopentenyl diacrylate, di(meth)acryloyl isocyanurate, and ethoxylated bisphenol A diacrylate (BPAEODE).
[0057] Examples of trifunctional (meth)acrylates include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tris(acryloyloxyethyl)isocyanurate.
[0058] Examples of tetrafunctional or higher polyfunctional (meth)acrylates include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, alkyl-modified dipentaerythritol pentaacrylate, and dipentaerythritol hexa(meth)acrylate.
[0059] The polyfunctional polymerizable compound may be used alone or in combination of two or more kinds. The polyfunctional polymerizable compound is preferably at least one selected from the group consisting of dipentaerythritol hexaacrylate (DPHA) and 1,9-nonanediol diacrylate (NDDA).
[0060] The amount of the polyfunctional polymerizable compound in the polymerizable component is preferably 0.01 to 2 parts by mass, more preferably 0.03 to 1.5 parts by mass, and even more preferably 0.05 to 1.2 parts by mass, relative to 100 parts by mass of the monofunctional monomer. When the amount of the polyfunctional polymerizable compound is equal to or more than the lower limit, the cohesive force of the pressure-sensitive adhesive sheet 10 can be increased, and the adhesive reliability after being attached to the adherend can be improved. When the amount of the polyfunctional polymerizable compound is equal to or less than the upper limit, the wettability of the pressure-sensitive adhesive sheet 10 to the adherend can be ensured, and the initial adhesive strength of the pressure-sensitive adhesive sheet 10 to the adherend can be ensured.
[0061] In this embodiment, the acrylic polymer is formed by photopolymerization of the polymerizable components. The polymerizable components (including a monofunctional monomer and a polyfunctional polymerizable compound as a crosslinking agent) may be polymerized in one step or in multiple steps. In the multistep polymerization method, a prepolymer composition containing a partial polymer (a mixture of a polymer of a monofunctional monomer and an unreacted monofunctional monomer) is first prepared by polymerizing a monofunctional monomer (preliminary polymerization). Next, a polyfunctional polymerizable compound as a crosslinking agent is added to the prepolymer composition, and then a polymerization reaction is allowed to proceed in a reaction system containing the partial polymer and the polyfunctional polymerizable compound (main polymerization). In the photopolymerization, a photopolymerization initiator may be used.
[0062] Examples of the photopolymerization initiator include a radical photopolymerization initiator, a cationic photopolymerization initiator, and an anionic photopolymerization initiator.
[0063] Examples of the radical photopolymerization initiator include an acylphosphine oxide photopolymerization initiator, a benzoin ether photopolymerization initiator, an acetophenone photopolymerization initiator, an α-ketol photopolymerization initiator, and an aromatic sulfonyl chloride photopolymerization initiator.
[0064] Examples of the acylphosphine oxide photopolymerization initiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of the benzoin ether photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-1,2-diphenylethan-1-one. Examples of the acetophenone photopolymerization initiator include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. Examples of the α-ketol photopolymerization initiator include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one. Examples of the aromatic sulfonyl chloride photopolymerization initiator include 2-naphthalenesulfonyl chloride. The photopolymerization initiator may be used alone or in combination of two or more kinds. The photopolymerization initiator is preferably at least one selected from the group consisting of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,2-dimethoxy-2-phenylacetophenone, and 1-hydroxycyclohexyl phenyl ketone.
[0065] The amount of the photopolymerization initiator is preferably 0.03 to 0.5 parts by mass, more preferably 0.06 to 0.3 parts by mass, and even more preferably 0.08 to 0.2 parts by mass, relative to 100 parts by mass of the polymerizable component. The amount of the photopolymerization initiator is preferably 0.03 parts by mass or more, more preferably 0.06 parts by mass or more, and even more preferably 0.08 parts by mass or more, relative to 100 parts by mass of the polymerizable component. When the amount of the photopolymerization initiator is equal to or more than the above lower limit, a crosslinked network with sufficient crosslinking density is formed in the acrylic polymer, and the adhesive strength of the adhesive sheet 10 can be ensured. The amount of the photopolymerization initiator is preferably 0.5 parts by mass or less, more preferably 0.3 parts by mass or less, and even more preferably 0.2 parts by mass or less, relative to 100 parts by mass of the polymerizable component. When the amount of the photopolymerization initiator is equal to or less than the above upper limit, cohesive failure of the adhesive surface of the adhesive sheet 10 can be suppressed when the adhesive sheet 10 is peeled off from the adherend. This is useful, for example, for ensuring alcohol reworkability. When the acrylic polymer is photopolymerized by preliminary polymerization and main polymerization, a photopolymerization initiator may be added after the preliminary polymerization and during the main polymerization.
[0066] From the viewpoint of ensuring the cohesive force of the adhesive sheet 10, the weight average molecular weight of the base polymer is preferably 100,000 to 5,000,000, more preferably 300,000 to 3,000,000, and even more preferably 500,000 to 2,000,000. The weight average molecular weight of the base polymer is preferably 100,000 or more, more preferably 300,000 or more, and even more preferably 500,000 or more. When the weight average molecular weight of the base polymer is equal to or more than the above lower limit, the cohesive force of the adhesive sheet 10 can be ensured. The weight average molecular weight of the base polymer is preferably 5,000,000 or less, more preferably 3,000,000 or less, and even more preferably 2,000,000 or less. When the weight average molecular weight of the base polymer is equal to or less than the above upper limit, the flexibility of the adhesive sheet 10 can be ensured. The weight average molecular weight of the acrylic polymer is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.
[0067] The glass transition temperature (Tg) of the base polymer is preferably 0° C. or lower, more preferably −10° C. or lower, and even more preferably −20° C. or lower. The glass transition temperature is, for example, −80° C. or higher. That is, the glass transition temperature of the base polymer is preferably −80° C. to 0° C., more preferably −80° C. to −10° C., and even more preferably −80° C. to −20° C.
[0068] The glass transition temperature of the base polymer may be determined by the following Fox formula (theoretical value). The Fox formula is a relational expression between the glass transition temperature Tg of a polymer and the glass transition temperature Tgi of a homopolymer of a monomer constituting the polymer. In the following Fox formula, Tg represents the glass transition temperature (°C) of a polymer, Wi represents the weight fraction of a monomer i constituting the polymer, and Tgi represents the glass transition temperature (°C) of a homopolymer formed from the monomer i. The glass transition temperature of a homopolymer may be determined by a literature value. For example, the glass transition temperatures of various homopolymers are listed in "Polymer Handbook" (4th edition, John Wiley & Sons, Inc., 1999). On the other hand, the glass transition temperature of a homopolymer of a monomer may be determined by a method specifically described in JP-A-2007-51271.
[0069] Fox formula 1 / (273+Tg)=Σ[Wi / (273+Tgi)]
[0070] The hydrogen bond term ΔH of the Hansen solubility parameter (HSP) of the base polymer is preferably 3.5 or more, preferably 3.8 or more, preferably 4.0 or more, from the viewpoint of ensuring the alcohol affinity of the pressure-sensitive adhesive sheet 10. The hydrogen bond term ΔH of the HSP of the base polymer is preferably 4.9 or less, preferably 4.7 or less, preferably 4.6 or less, from the viewpoint of suppressing the hydrophilicity of the pressure-sensitive adhesive sheet 10. The hydrogen bond term ΔH of the HSP of the base polymer is preferably 3.5 to 4.9, preferably 3.8 to 4.7, preferably 4.0 to 4.6, from the viewpoint of simultaneously ensuring the alcohol affinity and suppressing the hydrophilicity of the pressure-sensitive adhesive sheet 10. Examples of methods for adjusting the ΔH of the base polymer include adjusting the monomer composition of the base polymer.
[0071] The Hansen Solubility Parameter (HSP) is expressed by the following formula (1), in which δH is the hydrogen bond term that represents the energy derived from the hydrogen bond forces between molecules, δD is the dispersion term that represents the energy derived from the dispersion forces between molecules, and δP is the polarization term that represents the energy derived from the polar forces between molecules.
[0072] HSP = (δD 2 +δP 2 +δH 2 ) 1 / 2 (1)
[0073] The δH of a polymer is determined by the ratio of the monomers m i Mole fraction x i and the monomer m i Hydrogen bond term δh i From the above, it can be calculated by the following formula (2). The hydrogen bond term Δh of the monomer can be calculated, for example, by computer software HSPiP (Hansen Solubility Parameters in Practice). The method of calculating ΔH is specifically described below in the examples.
[0074] δH=Σ x i ×δh i (2)
[0075] The polarization term ΔP of the HSP of the base polymer is preferably 2.5 or more, preferably 2.8 or more, preferably 3.0 or more, from the viewpoint of ensuring the alcohol affinity of the pressure-sensitive adhesive sheet 10. The polarization term ΔP of the HSP of the base polymer is preferably 3.7 or less, preferably 3.5 or less, preferably 3.3 or less, from the viewpoint of suppressing the hydrophilicity of the pressure-sensitive adhesive sheet 10. The polarization term ΔP of the HSP of the base polymer is preferably 2.5 to 3.7, preferably 2.8 to 3.5, preferably 3.0 to 3.3, from the viewpoint of both ensuring the alcohol affinity of the pressure-sensitive adhesive sheet 10 and suppressing the hydrophilicity. An example of a method for adjusting ΔP of the base polymer is adjustment of the monomer composition of the base polymer. ΔP of a polymer is determined by the amount of monomer m forming the polymer. i Mole fraction x i and the monomer m i The polarization term δp i From this, it can be calculated by the following formula (3). The polarization term Δp of the monomer can be calculated, for example, by computer software HSPiP (Hansen Solubility Parameters in Practice). The method of calculating ΔP is specifically as described later in the Examples.
[0076] δP=Σ x i ×δp i (3)
[0077] The content of the base polymer in the pressure-sensitive adhesive sheet 10 is preferably 80 to 99.9% by mass, more preferably 85 to 99.5% by mass, and even more preferably 90 to 99.0% by mass. The content of the base polymer in the pressure-sensitive adhesive sheet 10 is preferably 80% by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more. When the content of the base polymer is equal to or more than the above lower limit, the pressure-sensitive adhesive sheet 10 can appropriately exhibit basic properties such as adhesiveness. The content of the base polymer in the pressure-sensitive adhesive sheet 10 is preferably 99.9% by mass or less, more preferably 99.5% by mass or less, and even more preferably 99.0% by mass or less. When the content of the base polymer is equal to or less than the above upper limit, the content of the oligomer described below can be ensured.
[0078] The pressure-sensitive adhesive sheet 10 may contain an oligomer. Examples of the oligomer include hydrophilic oligomers and hydrophobic oligomers. The hydrophilic oligomer refers to an oligomer as a polymer of a monomer component containing 3% by mass or more of a hydrophilic monomer. The hydrophobic oligomer refers to an oligomer as a polymer of a monomer component containing less than 3% by mass of a hydrophilic monomer. The weight-average molecular weight of the oligomer is, for example, 1000 or more and 30000 or less. The weight-average molecular weight of the oligomer is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.
[0079] When the base polymer is an acrylic polymer, the oligomer is preferably an acrylic oligomer. That is, the hydrophilic oligomer is preferably a hydrophilic acrylic oligomer. The hydrophobic oligomer is preferably a hydrophobic acrylic oligomer. The acrylic oligomer is an oligomer as a polymer of a monomer component containing 50% by mass or more of (meth)acrylic acid alkyl ester.
[0080] The hydrophilic acrylic oligomer is preferably a polymer of monomer components including a (meth)acrylic acid alkyl ester (chain alkyl (meth)acrylate) having a chain alkyl group, a (meth)acrylic acid alkyl ester (alicyclic alkyl (meth)acrylate) having an alicyclic alkyl group, and a hydrophilic monomer. Specific examples of the (meth)acrylic acid alkyl ester include the (meth)acrylic acid alkyl esters described above as monomer components of the acrylic polymer. Examples of the hydrophilic monomer include hydroxyl group-containing monomers and carboxyl group-containing monomers. Specific examples of the hydroxyl group-containing monomers and carboxyl group-containing monomers include the hydroxyl group-containing monomers and carboxyl group-containing monomers described above as monomer components of the acrylic polymer.
[0081] The linear alkyl (meth)acrylate is preferably methyl methacrylate (MMA) since it has a high glass transition temperature and is relatively compatible with the base polymer. The alicyclic alkyl (meth)acrylate is preferably at least one selected from the group consisting of dicyclopentanyl acrylate (DCPA), dicyclopentanyl methacrylate (DCPMA), cyclohexyl acrylate (CHA), and cyclohexyl methacrylate (CHMA). The hydrophilic monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl methacrylate (HEMA), 2-hydroxypropyl methacrylate (HPMA), and 4-hydroxybutyl methacrylate (HBMA). That is, the acrylic oligomer is preferably a polymer of monomer components including at least one selected from the group consisting of DCPA, DCPMA, CHA, and CHMA, at least one selected from the group consisting of HEMA, HPMA, and HBMA, and MMA.
[0082] The proportion of alicyclic alkyl (meth)acrylate in the monomer component of the hydrophilic acrylic oligomer is preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and also preferably 80% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less. The proportion of alicyclic alkyl (meth)acrylate being equal to or greater than the above lower limit helps to ensure the adhesive strength and cohesive strength of the pressure-sensitive adhesive sheet 10. The proportion of alicyclic alkyl (meth)acrylate being equal to or less than the above upper limit helps to ensure the compatibility of the acrylic polymer and the hydrophilic oligomer in the pressure-sensitive adhesive sheet 10. The proportion of chain alkyl (meth)acrylate in the monomer component of the hydrophilic acrylic oligomer is preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and also preferably 80% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less. The proportion of the chain alkyl (meth)acrylate being equal to or greater than the above lower limit helps to ensure the compatibility of the acrylic polymer and the hydrophilic oligomer in the pressure-sensitive adhesive sheet 10. The proportion of the chain alkyl (meth)acrylate being equal to or less than the above upper limit helps to ensure the adhesive strength and cohesive strength of the pressure-sensitive adhesive sheet 10. The proportion of the hydrophilic monomer in the monomer component of the hydrophilic acrylic oligomer is preferably 6% by mass or more, more preferably 8% by mass or more, even more preferably 10% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 12% by mass or less. When the proportion of the hydrophilic monomer is equal to or greater than the above lower limit, the adhesive strength and cohesive strength of the pressure-sensitive adhesive sheet 10 can be ensured. When the proportion of the hydrophilic monomer is equal to or less than the above upper limit, the compatibility of the acrylic polymer and the hydrophilic oligomer in the pressure-sensitive adhesive sheet 10 can be ensured.
[0083] The hydrophilic acrylic oligomer is obtained by polymerizing the monomer components of the acrylic oligomer (the same applies to the hydrophobic acrylic oligomer described below). Examples of the polymerization method include solution polymerization, active energy ray polymerization (e.g., UV polymerization), bulk polymerization, and emulsion polymerization. In the polymerization of the acrylic oligomer, a polymerization initiator may be used, and a chain transfer agent may be used for the purpose of adjusting the molecular weight.
[0084] The content of the hydrophilic oligomer in the pressure-sensitive adhesive sheet 10 is preferably 0.1 to 3 parts by mass, more preferably 0.3 to 2 parts by mass, and even more preferably 0.4 to 1.2 parts by mass, based on 100 parts by mass of the base polymer. The content of the hydrophilic oligomer in the pressure-sensitive adhesive sheet 10 is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and even more preferably 0.4 parts by mass or more. When the content of the hydrophilic oligomer is equal to or more than the above lower limit, the adhesive strength of the pressure-sensitive adhesive sheet 10 (particularly the adhesive strength under a high humidity environment) can be increased. The content of the hydrophilic oligomer in the pressure-sensitive adhesive sheet 10 is preferably 3 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 1.2 parts by mass or less, based on 100 parts by mass of the base polymer. When the content of the hydrophilic oligomer is equal to or less than the above upper limit, the transparency of the pressure-sensitive adhesive sheet 10 can be ensured. When the amount of oligomer in the pressure-sensitive adhesive sheet 10 is too large, the compatibility of the oligomer decreases, and the haze tends to increase and the transparency tends to decrease.
[0085] The hydrophobic acrylic oligomer is preferably a polymer of monomer components including a chain alkyl (meth)acrylate and an alicyclic alkyl (meth)acrylate. The chain alkyl (meth)acrylate is preferably MMA because it has a high glass transition temperature and is relatively compatible with the base polymer. The alicyclic alkyl (meth)acrylate is preferably at least one selected from the group consisting of dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate. That is, the acrylic oligomer is preferably a polymer of monomer components including one or more selected from the group consisting of dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate, and MMA.
[0086] The proportion of alicyclic alkyl (meth)acrylate in the monomer component of the hydrophobic acrylic oligomer is preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and also preferably 90% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less. The proportion of alicyclic alkyl (meth)acrylate being equal to or greater than the above lower limit helps to ensure the adhesive strength and cohesive strength of the pressure-sensitive adhesive sheet 10. The proportion of alicyclic alkyl (meth)acrylate being equal to or less than the above upper limit helps to ensure the compatibility of the acrylic polymer and the hydrophobic oligomer in the pressure-sensitive adhesive sheet 10. The proportion of chain alkyl (meth)acrylate in the monomer component of the hydrophobic acrylic oligomer is preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and also preferably 90% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less. Having the proportion of the chain alkyl (meth)acrylate equal to or greater than the above lower limit helps ensure compatibility between the acrylic polymer and the hydrophobic oligomer in the pressure-sensitive adhesive sheet 10. Having the proportion of the chain alkyl (meth)acrylate equal to or less than the above upper limit helps ensure the adhesive strength and cohesive strength of the pressure-sensitive adhesive sheet 10.
[0087] The content of the hydrophobic oligomer in the pressure-sensitive adhesive sheet 10 is preferably 0.1 to 3 parts by mass, more preferably 0.3 to 2 parts by mass, and even more preferably 0.4 to 1.2 parts by mass, based on 100 parts by mass of the base polymer. The content of the hydrophobic oligomer in the pressure-sensitive adhesive sheet 10 is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and even more preferably 0.4 parts by mass or more. When the content of the hydrophobic oligomer is equal to or more than the above lower limit, the adhesive strength of the pressure-sensitive adhesive sheet 10 can be increased. The content of the hydrophobic oligomer in the pressure-sensitive adhesive sheet 10 is preferably 3 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 1.2 parts by mass or less, based on 100 parts by mass of the base polymer. When the content of the hydrophobic oligomer is equal to or less than the above upper limit, the transparency of the pressure-sensitive adhesive sheet 10 can be ensured.
[0088] The total content of the hydrophilic oligomer and the hydrophobic oligomer in the pressure-sensitive adhesive sheet 10 is, relative to 100 parts by mass of the base polymer, preferably 0.2 parts by mass or more, more preferably 0.6 parts by mass or more, even more preferably 0.8 parts by mass or more, and is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, even more preferably 3 parts by mass or less. When the total content of the oligomers is equal to or more than the above lower limit, the adhesive strength of the pressure-sensitive adhesive sheet 10 can be increased. When the total content of the oligomers is equal to or less than the above upper limit, the transparency of the pressure-sensitive adhesive sheet 10 can be ensured.
[0089] The pressure-sensitive adhesive sheet 10 may contain other components, such as a silane coupling agent, an ultraviolet absorbing agent, an antioxidant, a surfactant, and an anti-rust agent.
[0090] Examples of the silane coupling agent include silane coupling agents containing an epoxy group. Examples of the silane coupling agent containing an epoxy group include 3-glycidoxydialkyldialkoxysilane and 3-glycidoxyalkyltrialkoxysilane. Examples of the 3-glycidoxydialkyldialkoxysilane include 3-glycidoxypropylmethyldimethoxysilane and 3-glycidoxypropylmethyldiethoxysilane. Examples of the 3-glycidoxyalkyltrialkoxysilane include 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane. As the silane coupling agent, preferably, 3-glycidoxyalkyltrialkoxysilane is used, and more preferably, 3-glycidoxypropyltrimethoxysilane is used. The silane coupling agent may be used alone or in combination of two or more kinds. The proportion of the silane coupling agent in the adhesive sheet 10 is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, even more preferably 0.3 mass% or more, from the viewpoint of suppressing the adhesion of the adhesive sheet 10 to glass and exhibiting good alcohol peelability, and is preferably 3 mass% or less, more preferably 2 mass% or less, even more preferably 1 mass% or less.
[0091] The pressure-sensitive adhesive sheet 10 preferably does not contain a surfactant. From the viewpoint of ensuring the adhesive strength of the pressure-sensitive adhesive sheet 10 in a high-humidity environment, the content of the surfactant in the pressure-sensitive adhesive sheet 10 is preferably 0.3 mass % or less, more preferably 0.2 mass % or less, even more preferably 0.1 mass % or less, and particularly preferably 0.0 mass %.
[0092] Examples of the release liner L1 include a release liner having a release treatment layer on the surface of a liner substrate, and a release liner formed from a low-adhesion material. Examples of the liner substrate include a resin film and paper. Examples of the resin of the resin film include a polyester resin and a polycarbonate resin. Examples of the polyester resin include polyethylene terephthalate (PET) and polybutylene terephthalate. The release treatment layer can be formed by surface treating the liner substrate with a release treatment agent. Examples of the release treatment agent include a silicone release treatment agent, a long-chain alkyl release treatment agent, and a fluorine release treatment agent. Examples of the low-adhesion material include a polyolefin resin and a fluorine-based polymer. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). Examples of the fluorine-based polymer include polytetrafluoroethylene.
[0093] Examples of the release liner L2 include a release liner having a release treatment layer on the surface of a liner substrate and a release liner made of a low-adhesion material. Specifically, the release liner L2 is the same as that described above for the release liner L1.
[0094] The adhesive sheet 10 can be produced, for example, as follows.
[0095] First, a prepolymer composition is prepared. Specifically, a mixture (liquid) containing the monofunctional monomer for forming the base polymer and a photopolymerization initiator is prepared. Next, the mixture is irradiated with ultraviolet light to photopolymerize a portion of the monofunctional monomer in the mixture to obtain a prepolymer composition. Examples of light sources for ultraviolet light irradiation include ultraviolet LED lights, black light lamps, high-pressure mercury lamps, and metal halide lamps. In the ultraviolet light irradiation, the illuminance is, for example, 5 to 200 mW / cm. 2 The cumulative irradiation dose is, for example, 100 to 5000 mJ / cm 2The ultraviolet irradiation is preferably continued until the viscosity of the composition reaches about 15 to 25 Pa·s. This viscosity is measured using a Brookfield viscometer with a No. 5 rotor at a rotor speed of 10 rpm and at a temperature of 30°C. The prepolymer composition contains a photopolymerized product of a monofunctional monomer and an unreacted monofunctional monomer (residual monomer). The prepolymer composition does not contain a solvent.
[0096] Next, a multifunctional polymerizable compound (crosslinking agent) and other components as necessary are added to the prepolymer composition to prepare a pressure-sensitive adhesive composition. The other components include, for example, an oligomer, an additional photopolymerization initiator, a silane coupling agent, an antioxidant, and a rust inhibitor. This pressure-sensitive adhesive composition does not contain a solvent. That is, the pressure-sensitive adhesive composition prepared in this process is a solventless pressure-sensitive adhesive composition.
[0097] Next, a pressure-sensitive adhesive composition is applied onto the release liner L1 to form a coating film, and then a release liner L2 is laminated onto the coating film on the release liner L1. Examples of methods for applying the pressure-sensitive adhesive composition include roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and die coating.
[0098] Next, the coating film between the release liners L1 and L2 is irradiated with ultraviolet light to photocure it, forming an adhesive layer. The ultraviolet light irradiation causes a polymerization reaction in the coating film in a reaction system containing the residual monomer and the polyfunctional polymerizable compound, forming a first photopolymerized polymer having a photocrosslinked structure. Thereafter, the adhesive layer may be dried by heating. The drying temperature is, for example, 80°C to 150°C. The drying time is, for example, 30 seconds to 10 minutes. The drying process allows the unreacted monomer in the adhesive layer to be volatilized and removed.
[0099] In this manner, adhesive sheet 10 can be manufactured in which adhesive surfaces 11, 12 are covered and protected by release liners L1, L2. Release liners L1, L2 are peeled off from adhesive sheet 10 as necessary when adhesive sheet 10 is to be used.
[0100] The pressure-sensitive adhesive sheet 10 can be formed from a solvent-free pressure-sensitive adhesive composition. Such a pressure-sensitive adhesive sheet 10 is suitable for reducing the environmental load. That is, the pressure-sensitive adhesive sheet 10 formed from a solvent-free pressure-sensitive adhesive composition is environmentally friendly and preferable from the viewpoint of sustainable development.
[0101] The thickness of the pressure-sensitive adhesive sheet 10 is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more, from the viewpoint of ensuring sufficient adhesion to the adherend. The thickness of the pressure-sensitive adhesive sheet 10 is preferably 300 μm or less, more preferably 200 μm or less, and even more preferably 100 μm or less, from the viewpoint of ease of handling and thinning of the pressure-sensitive adhesive sheet 10. The thickness of the pressure-sensitive adhesive sheet 10 is preferably 10 to 300 μm, more preferably 20 to 200 μm, and even more preferably 30 to 100 μm, from the viewpoint of achieving both the above-mentioned adhesion and the above-mentioned ease of handling and thinning.
[0102] The total light transmittance of the pressure-sensitive adhesive sheet 10 is preferably 90% or more, more preferably 95% or more, and is, for example, 100% or less, from the viewpoint of ensuring the transparency of the pressure-sensitive adhesive sheet 10. The total light transmittance can be measured in accordance with JIS K 7375 (2008).
[0103] 4A to 4C show an example of a method of using the adhesive sheet 10. FIG.
[0104] In this method, first, as shown in Fig. 4A, the adhesive sheet 10 is attached to one surface in the thickness direction H of a member 31 (first adherend) (attaching step). Examples of the member 31 include a pixel panel and a polarizing film in a display panel. Through this step, the adhesive sheet 10 for bonding to another member is provided on the member 31.
[0105] 4B, the member 31 and a member 32 (second adherend) are joined via the adhesive sheet 10 on the member 31 (joining step). An example of the member 32 is a cover film in a display panel.
[0106] Next, as shown in Fig. 4C, the adhesive sheet 10 between the members 31 and 32 is aged (aging step). This step enhances the bonding strength between the adhesive sheet 10 and the members 31 and 32. The aging temperature is, for example, 20°C to 160°C. The aging time is, for example, 1 minute to 21 days. When autoclaving (heat and pressure treatment) is used for aging, the temperature is, for example, 30°C to 80°C, the pressure is, for example, 0.1 to 0.8 MPa, and the treatment time is, for example, 15 minutes or longer.
[0107] According to the adhesive sheet 10, after the bonding step or the aging step, the bonded state between the members 31, 32 can be easily released by using alcohol (alcohol rework) as necessary. Specifically, this is as follows.
[0108] By infiltrating alcohol into the interface between the member 31 and the adhesive sheet 10, the adhesive strength of the adhesive sheet 10 to the member 31 is reduced, and then the member 32 with the adhesive sheet 10 can be easily separated from the member 31. Thereafter, for example, a replacement member 32 with the adhesive sheet 10 can be bonded to the member 31 via the adhesive sheet 10. Alternatively, by infiltrating alcohol into the interface between the member 32 and the adhesive sheet 10, the adhesive strength of the adhesive sheet 10 to the member 32 is reduced, and then the member 31 with the adhesive sheet 10 can be easily separated from the member 32. Thereafter, for example, the replacement member 31 with the adhesive sheet 10 can be bonded to the member 32 via the adhesive sheet 10. Examples of alcohol include methanol, ethanol, propanol, and butanol.
[0109] According to the adhesive sheet 10, the adhesive strength Fa in the first ethanol peeling test 1 Since the thickness is 3.0 / 25 mm or less, the above alcohol rework is possible.
[0110] The adhesive sheet 10 is, for example, an optical adhesive sheet arranged at a light passing portion of a display panel. Examples of the display panel include a liquid crystal panel and an organic EL panel. The display panel has a laminated structure including elements such as a pixel panel, a polarizing film, a touch panel, and a cover film. The adhesive sheet 10 is used, for example, in the manufacturing process of the display panel to bond elements included in the laminated structure. EXAMPLES
[0111] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples. In addition, the specific numerical values of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding to those described in the above-mentioned "Form for carrying out the invention".
[0112] <Oligomer M 1 Preparation of First, in a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, a mixture containing 60 parts by mass of dicyclopentanyl methacrylate (DCPMA), 40 parts by mass of methyl methacrylate (MMA), 3.5 parts by mass of α-thioglycerol as a chain transfer agent, and 100 parts by mass of toluene as a polymerization solvent was stirred under a nitrogen atmosphere at 70°C for 1 hour. Next, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator was added to the mixture to prepare a reaction solution, which was reacted under a nitrogen atmosphere at 70°C for 2 hours and then at 80°C for 2 hours (polymerization reaction). Next, the reaction solution was heated at 130°C to volatilize and remove the toluene, chain transfer agent, and unreacted monomer. As a result, a solid acrylic oligomer (oligomer M 1 ) was obtained. Oligomer M 1The weight average molecular weight of oligomer M was 5100 and the glass transition temperature was 130°C. 1 is a hydrophobic oligomer.
[0113] <Oligomer M 2 Preparation of First, in a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, a mixture containing 45 parts by mass of DCPMA, 45 parts by mass of MMA, 10 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 3.5 parts by mass of α-thioglycerol as a chain transfer agent, and 100 parts by mass of toluene as a polymerization solvent was stirred at 70°C for 1 hour under a nitrogen atmosphere. Next, 0.2 parts by mass of AIBN as a thermal polymerization initiator was added to the mixture to prepare a reaction solution, which was reacted at 70°C for 2 hours and then at 80°C for 2 hours under a nitrogen atmosphere (polymerization reaction). Next, the reaction solution was heated at 130°C to volatilize and remove the toluene, chain transfer agent, and unreacted monomer. As a result, a solid acrylic oligomer (oligomer M 2 ) was obtained. Oligomer M 2 The weight average molecular weight of oligomer M was 5,300 and the glass transition temperature was 115°C. 2 is a hydrophilic oligomer.
[0114] Example 1 Preparation of Prepolymer Composition First, in a flask, 58 parts by mass of 2-ethylhexyl acrylate (2EHA), 39 parts by mass of acrylic laurate (LA), 3 parts by mass of 4-hydroxybutyl acrylate (4HBA), 0.05 parts by mass of a first photopolymerization initiator (product name "Omnirad184", 1-hydroxycyclohexyl phenyl ketone, manufactured by IGM Resins), and 0.05 parts by mass of a second photopolymerization initiator (product name "Omnirad651", 2,2-dimethoxy-2-phenylacetophenone, manufactured by IGM Resins) were mixed, and then the mixture was irradiated with ultraviolet light under a nitrogen atmosphere to polymerize a part of the monomer components in the mixture, thereby obtaining a prepolymer composition with a polymerization rate of about 10%. This prepolymer composition is a partial polymer containing a photopolymerized product (photopolymerized polymer P1a) and an unreacted monomer component (residual monomer).
[0115] Preparation of Pressure-Sensitive Adhesive Composition Next, 100 parts by mass of the prepolymer composition and oligomer M 1 1.0 part by mass of the adhesive composition C1 was obtained by mixing 0.06 part by mass of dipentaerythritol hexaacrylate (DPHA) (product name "KAYARAD DPHA", manufactured by Nippon Kayaku Co., Ltd.) as a multifunctional polymerizable compound, and 0.3 part by mass of a silane coupling agent (product name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.).
[0116] <Preparation of Adhesive Sheet> Next, the adhesive composition C1 was applied onto the release-treated surface of a first release liner (product name "Diafoil MRF", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side to form a coating film. Next, the release-treated surface of a second release liner (product name "Diafoil MRN", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side was attached onto the coating film on the first release liner. Next, the coating film between the release liners was irradiated with ultraviolet light from the second release liner side, and the coating film was photocured to form an adhesive layer with a thickness of 50 μm (ultraviolet light irradiation step). For ultraviolet light irradiation, a black light lamp (manufactured by Toshiba) was used as the light source, and the illuminance was set to 5.0 mW / cm. 2 The cumulative irradiation dose was 1500 mJ / cm2 In the ultraviolet irradiation step, a photopolymerization reaction proceeds in the coating film in a reaction system containing the residual monomer and the polyfunctional polymerizable compound, and a photopolymerized polymer P1b having a photocrosslinked structure is formed. In addition, since the photopolymerization reaction proceeds around the photopolymerized polymer P1a, the photopolymerized polymer P1b is formed around the photopolymerized polymer P1a. The pressure-sensitive adhesive layer formed in this step contains such photopolymerized polymer P1a and photopolymerized polymer P1b as base polymers.
[0117] Next, after peeling the first release liner from the adhesive layer, the adhesive layer on the second release liner was dried in a hot air oven at 130°C for 3 minutes. This caused the unreacted monomer in the adhesive layer to volatilize and be removed. Then, after cooling at room temperature, the release-treated surface of a third release liner (product name "Diafoil MRF", thickness 38μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side was attached to the adhesive layer on the second release liner.
[0118] In this manner, the pressure-sensitive adhesive sheet with release liner of Example 1 (second release liner / pressure-sensitive adhesive sheet (thickness 50 μm) / third release liner) was produced.
[0119] Example 2 The PSA sheet with release liner of Example 2 was produced in the same manner as the PSA sheet with release liner of Example 1, except for the following: In the preparation of the PSA composition, oligomer M 1 The blending amount of oligomer M is 0.5 parts by mass. 2 0.5 parts by mass was blended.
[0120] Example 3 The PSA sheet with release liner of Example 3 was produced in the same manner as the PSA sheet with release liner of Example 1, except for the following: In preparing the prepolymer composition, the blend amount of 2EHA was 56 parts by mass, and 2 parts by mass of N-vinyl-2-pyrrolidone (NVP) was also blended.
[0121] Example 4 The PSA sheet with release liner of Example 4 was produced in the same manner as the PSA sheet with release liner of Example 1, except for the following: In preparing the prepolymer composition, the blended amount of 2EHA was 52 parts by mass, and the blended amount of 4HBA was 9 parts by mass.
[0122] Example 5 The PSA sheet with release liner of Example 5 was produced in the same manner as the PSA sheet with release liner of Example 1, except for the following: The composition of the prepolymer composition was changed to the composition shown in Table 1. In the preparation of the PSA composition, oligomer M 1 Instead of oligomer M 2 1.0 part by mass of DPHA was blended, 0.08 part by mass of 1,9-nonanediol diacrylate (NDDA) (product name "Viscoat #260", manufactured by Osaka Organic Chemical Industry Co., Ltd.) was blended in place of DPHA, and 0.1 part by mass of a first additional photopolymerization initiator (Omnirad651) was blended.
[0123] Comparative Example 1 In the preparation of the prepolymer composition, oligomer M 1 An adhesive sheet with a release liner of Comparative Example 1 was produced in the same manner as the adhesive sheet with a release liner of Example 1, except that no compound was added.
[0124] Comparative Example 2 Preparation of Prepolymer Composition In a flask, a monomer mixture of 70 parts by mass of n-octyl acrylate (NOAA), 20 parts by mass of n-butyl acrylate (BA), 8 parts by mass of 4HBA, and 2 parts by mass of NVP was mixed with 0.05 parts by mass of a first photopolymerization initiator (Omnirad184) and 0.05 parts by mass of a third photopolymerization initiator (product name "Omnirad819", bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, manufactured by IGM Resins). The mixture was then irradiated with ultraviolet light under a nitrogen atmosphere to polymerize a portion of the monomer components in the mixture, thereby obtaining a prepolymer composition with a polymerization rate of approximately 10%.
[0125] Preparation of Pressure-Sensitive Adhesive Composition Next, 100 parts by mass of the prepolymer composition and oligomer M 1 0.5 parts by weight of oligomer M 2 Adhesive composition C2 was prepared by mixing 0.5 parts by mass of a polyfunctional polymerizable compound, 0.01 parts by mass of DPHA (KAYARAD DPHA), 0.3 parts by mass of a first reactive surfactant (product name "Acrit 8WX-046-NS", manufactured by Taisei Fine Chemical Co., Ltd.), 0.1 parts by mass of a non-reactive surfactant (product name "Rheodol TW-L120", manufactured by Kao Corporation), and 0.04 parts by mass of a second additional photopolymerization initiator (Omnirad819).
[0126] <Preparation of Adhesive Sheet> An adhesive layer 50 μm thick was formed in the same manner as described above for Example 1, except that adhesive composition C2 was used instead of adhesive composition C1, and an adhesive sheet with release liner of Comparative Example 2 (second release liner / adhesive sheet (thickness 50 μm) / third release liner) was produced.
[0127] Comparative Example 3 An adhesive sheet with a release liner of Comparative Example 3 was produced in the same manner as the adhesive sheet with a release liner of Comparative Example 2, except for the following: In preparing the adhesive composition, the amount of DPHA blended was 0.02 parts by mass, no first reactive surfactant and no non-reactive surfactant were blended, and 0.3 parts by mass of a second reactive surfactant (product name "Aqualon KH-10", manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 0.1 parts by mass of a third reactive surfactant (product name "Aminoion RE3000MA", manufactured by Nippon Nyukazai Co., Ltd.) were blended.
[0128] Comparative Example 4 The PSA sheet with release liner of Comparative Example 4 was produced in the same manner as the PSA sheet with release liner of Comparative Example 2, except for the following: In the preparation of the PSA composition, oligomer M 1 The blending amount of oligomer M is 1.5 parts by mass. 2 The amount of DPHA was 0.045 parts by mass, and the first reactive surfactant and the non-reactive surfactant were not blended.
[0129] Comparative Example 5 The PSA sheet with release liner of Comparative Example 5 was produced in the same manner as the PSA sheet with release liner of Comparative Example 2, except for the following: In the preparation of the PSA composition, oligomer M 1 The blending amount of oligomer M is 1.5 parts by mass. 2 was not blended, the amount of DPHA was 0.11 parts by mass, 0.5 parts by mass of a silane coupling agent (KBM-403) was blended, and the amount of a second additional photopolymerization initiator (Omnirad819) was 0.02 parts by mass.
[0130] <Weight average molecular weight of oligomer> Oligomer M 1 ,M 2 The weight average molecular weight (Mw) of each of the above was measured by gel permeation chromatography (GPC) under the following measurement conditions, and was calculated in terms of polystyrene. A GPC measuring device (product name "HLC-8120GPC", manufactured by Tosoh Corporation) was used for the measurement. The sample solution was prepared as follows. First, a dimethylformamide (DMF) solution (salt added) with a sample concentration of 0.20 mass% was prepared using the acrylic oligomer as a sample, and the DMF solution was left to stand for 20 hours. Next, the DMF solution was filtered through a membrane filter with an average pore size of 0.45 μm, and the filtrate was obtained as a sample solution for molecular weight measurement.
[0131] [GPC measurement conditions] Columns: SuperAWM-H + SuperAW4000 + SuperAW2500, each TSKgel (Tosoh) Column temperature: 40℃ Eluent: DMF solution (salt added) Flow rate: 0.4mL / min Sample injection volume: 40 μL Standard sample: Polystyrene (Agilent) Detector: Differential refractometer (RI)
[0132] <HSP> For each acrylic polymer used in the examples and comparative examples, the hydrogen bond term δH, the dispersion term δD, and the polarization term δP of the Hansen solubility parameter (HSP) were determined. Specifically, they are as follows.
[0133] Regarding the hydrogen bond term δH, first, the hydrogen bond parameters m of each monomer forming the acrylic polymer were calculated using computer software HSPiP (Hansen Solubility Parameters in Practice). i For the hydrogen bond term of HSP (δh i Next, the monomer m i Mole fraction x i and the monomer m i Hydrogen bond term δh i From this, the hydrogen bond parameter (ΔH) of the acrylic polymer was calculated using the following formula (2).
[0134] δH=Σ x i ×δh i (2)
[0135] Similarly, for the dispersion term δD, the computer software HSPiP is used to calculate the dispersion of each monomer m i The variance term of HSP (δd i ) and the monomer m i Mole fraction x i and the monomer m i Dispersion term δd i The dispersion term (δD) of the acrylic polymer was calculated from the above. Similarly, the polarization term δP was calculated by using the computer software HSPiP to calculate the polarization term δP of each monomer m i For the HSP polarization term (δp i ) and the monomer m i Mole fraction x i and the monomer m i The polarization term δp iThe hydrogen bond term δH, dispersion term δD, and polarization term δP of the acrylic polymer are shown in Tables 1 and 2.
[0136] <Initial room temperature peeling test> For each of the pressure-sensitive adhesive sheets in the Examples and Comparative Examples, an initial room temperature peel test was carried out to measure the adhesive strength Fn 1 Specifically, the following was measured.
[0137] Preparation steps: First, the third release liner was peeled off from the adhesive sheet with release liner (second release liner / adhesive sheet / third release liner). Next, the adhesive sheet exposed by this was attached to a polyethylene terephthalate (PET) film (product name "Lumirror S10", thickness 50 μm, manufactured by Toray) whose surface had been plasma-treated. This resulted in a laminated film. In the plasma treatment, a plasma irradiation device (product name "AP-TO5", manufactured by Sekisui Kogyo Co., Ltd.) was used, and the voltage was set to 160 V, the frequency was set to 10 kHz, and the treatment speed was set to 5000 mm / min. In the lamination, the adhesive sheet was pressed against the PET film by moving a 2 kg hand roller back and forth once in an environment of 25°C. Next, a laminated film piece with a width of 25 mm and a length of 100 mm was cut out from the laminated film. This laminated film has a PET film, an adhesive sheet piece, and a second release liner in this order in the thickness direction. Next, the second release liner was peeled off from the adhesive sheet piece on the PET film, and the adhesive sheet piece (width 25 mm × length 100 mm) exposed thereby was attached to the tin surface of an alkali glass plate prepared by the float method to obtain a laminate.
[0138] Heat and pressure step: Next, the laminate was subjected to a heat and pressure treatment under conditions of 50° C., 0.5 MPa and 15 minutes, thereby causing the adhesive sheet piece to be pressure-bonded to the alkaline glass plate.
[0139] Settling step: The laminate was then allowed to stand at room temperature for 72 hours.
[0140] Measurement steps: Next, a 180° peel test was performed to peel the adhesive sheet piece from the alkali glass plate in the laminate, and the force required for peeling (peeling force) was measured. A tensile tester (product name "Autograph AG-50NX plus", manufactured by Shimadzu Corporation) was used for this measurement. Specifically, in this measurement, the adhesive sheet piece was peeled from the alkali glass plate by pulling one end in the length direction under conditions (first conditions) of 25°C, relative humidity 50%, peel angle 180°, and tensile speed 300 mm / min, to measure the peeling force. The peel length (total length) was set to 50 mm, and the average value of the peeling force measured between peel lengths of 10 mm and 40 mm was taken as the adhesive force.
[0141] The adhesive strength measured in the initial room temperature peel test step is called the adhesive strength Fn 1 The values are shown in Tables 1 and 2 as (N / 25mm).
[0142] <Room temperature peel test after storage> For each of the pressure-sensitive adhesive sheets in the Examples and Comparative Examples, a room temperature peel test was carried out after storage to measure the adhesive strength Fn 2 The room temperature peel test after storage was the same as the initial room temperature peel test, except that the laminate was left to stand at 50° C. for 168 hours in the standing step.
[0143] In the measurement step of the room temperature peel test after storage, the peel length (total length) was set to 50 mm, and the average value of the peel force measured between a peel length of 10 mm and 40 mm was taken as the adhesive force. The adhesive force measured in the measurement step of the room temperature peel test after storage was taken as the adhesive force Fn 2 The values are shown in Tables 1 and 2 as (N / 25mm).
[0144] <First ethanol peeling test> For each of the pressure-sensitive adhesive sheets in the Examples and Comparative Examples, a first ethanol peeling test was carried out to measure the adhesive strength Fa 1was measured. The first ethanol peeling test was the same as the initial room temperature peeling test, except for the following: In the standing step, the laminate was left standing at 50°C for 168 hours. After the standing step and before the measurement step, an ethanol supplying step was carried out. In the ethanol supplying step, 10 μL of ethanol was supplied onto the alkaline glass plate of the laminate so that the ethanol was in contact with one end of the adhesive sheet piece in the longitudinal direction at the interface between the alkaline glass plate and the adhesive sheet piece.
[0145] In the measurement step of the first ethanol peel test, the peel length d when the peel force begins to stabilize during the peeling process of the adhesive sheet piece is 1 and peel length d 1 The peel length d when the peel force increases by 10% compared to the peel force at 2 The peel length d 1 From peel length d 2 The average value of the peel strength measured up to this point was taken as the adhesive strength. The adhesive strength measured in the measurement step of the first ethanol peel test was taken as the adhesive strength Fa 1 The values are shown in Tables 1 and 2 as (N / 25mm).
[0146] <Second ethanol peeling test> A second ethanol peeling test was carried out on each of the pressure-sensitive adhesive sheets of the Examples and Comparative Examples to measure the adhesive strength Fa 2 The second ethanol peeling test was the same as the first ethanol peeling test, except for the following: In the standing step, the laminate was stood at room temperature for 72 hours.
[0147] In the measurement step of the second ethanol peeling test, the peel length d when the peel force starts to stabilize during the peeling process is 1 and peel length d 1 The peel length d when the peel force increases by 10% compared to the peel force at 2 and determine the peel length d 1 From peel length d 2 The average value of the peel strength measured up to this point was taken as the adhesive strength. The adhesive strength measured in the measurement step of the second ethanol peel test was taken as the adhesive strength Fa 2 (N / 25mm) is shown in Tables 1 and 2. Peel length d2 and peel length d 1 Difference from (d 2 -d 1 ) is shown in Tables 1 and 2 as the ethanol peeling duration d (mm). 2 Adhesion strength to Fa 1 The fluctuation rate (%) is also shown in Tables 1 and 2. This fluctuation rate is calculated by the following formula.
[0148] Fluctuation rate (%) = [(Fa 1 -Fa 2 ) / Fa 2 ] x 100
[0149] <High temperature and high humidity peeling test> A high-temperature, high-humidity peel test was carried out on each of the pressure-sensitive adhesive sheets of the Examples and Comparative Examples to measure the adhesive strength Fh. The high-temperature, high-humidity peel test was the same as the initial room-temperature peel test, except for the following: In the standing step, the laminate was left standing at room temperature for 24 hours. After the standing step and before the measurement step, a high-temperature, high-humidity treatment step was carried out. In the high-temperature, high-humidity treatment step, the laminate after the standing step was subjected to high-temperature, high-humidity treatment under conditions of 60°C, relative humidity 93%, and 15 minutes. In the measurement step, a 180° peel test was carried out under second conditions of 60°C, relative humidity 93%, peel angle 180°, and tensile speed 300 mm / min, instead of the first conditions.
[0150] In the measurement step of the high temperature and high humidity peel test, the peel length (total length) was set to 50 mm, and the average peel force measured between peel lengths of 10 mm and 40 mm was taken as the adhesive strength. The adhesive strength measured in the measurement step of the high temperature and high humidity peel test is shown in Tables 1 and 2 as adhesive strength Fh (N / 25 mm).
[0151] <First water peeling test> For each of the comparative pressure-sensitive adhesive sheets, a first water peeling test was carried out to measure the adhesive strength Fw 1 The first water peeling test was the same as the second ethanol peeling test, except that the following water supplying step was carried out instead of the ethanol supplying step.
[0152] Water supply steps: After the standing step, 25 μL of water was supplied onto the alkaline glass plate of the laminate so that the water was in contact with one longitudinal end of the adhesive sheet piece at the interface between the alkaline glass plate and the adhesive sheet piece.
[0153] In the first water peel test, the peel length d when the peel force begins to stabilize during the peeling process is measured. 1 and peel length d 1 The peel length d when the peel force increases by 10% compared to the peel force at 2 and determine the peel length d 1 From peel length d 2 The average value of the peel strengths measured up to this point was taken as the adhesive strength. The adhesive strength measured in the measurement step of the first water peel test was taken as the adhesive strength Fw 1 The values are shown in Tables 1 and 2 as (N / 25mm).
[0154] <Second water peeling test> For each of the comparative pressure-sensitive adhesive sheets, a second water peeling test was carried out to measure the adhesive strength Fw 2 The second water peeling test was the same as the first ethanol peeling test, except that the above water supplying step was carried out instead of the ethanol supplying step.
[0155] In the measurement step of the second water peel test, the peel length d when the peel force starts to stabilize during the peel process is 1 and peel length d 1 The peel length d when the peel force increases by 10% compared to the peel force at 2 and determine the peel length d 1 From peel length d 2 The average value of the peel strength measured up to this point was taken as the adhesive strength. The adhesive strength measured in the measurement step of the second water peel test was taken as the adhesive strength Fw 2 The values are shown in Tables 1 and 2 as (N / 25mm).
[0156] A surfactant is used in the pressure-sensitive adhesive sheets of Comparative Examples 2 and 3. As a result, the pressure-sensitive adhesive sheets of Comparative Examples 2 and 3 have an adhesive strength Fw 1However, the adhesive sheets of Comparative Examples 2 and 3 have low adhesive strength Fh in the high temperature and high humidity peel test. Such adhesive sheets cannot ensure good bonding reliability in a high humidity environment. Furthermore, the adhesive sheets of Comparative Examples 2 and 3 have low adhesive strength Fw in the second water peel test. 2 But the adhesive strength Fw 1 That is, the pressure-sensitive adhesive sheets of Comparative Examples 2 and 3 cannot maintain water removability (have no long-term reworkability).
[0157] [Table 1]
[0158] [Table 2] [Explanation of symbols]
[0159] 10 Adhesive sheet (alcohol-peelable optical adhesive sheet) H Thickness direction 11,12 Adhesive surface 21 Acrylic glass plate 22 Ethanol L1, L2 Release liner
Claims
1. Contains a photopolymer as a base polymer, Adhesive strength Fn in the initial room temperature peel test below 1 is 9.0N / 25mm or more, Adhesive strength F in the first ethanol peeling test described below 1 is 3.0N / 25mm or less, An alcohol-peelable optical adhesive sheet having an adhesive strength Fh of 2.0 N / 25 mm or more in the high-temperature, high-humidity peel test described below. Initial room temperature peel test: First, a 25 mm wide x 100 mm long adhesive sheet piece of the alcohol-peelable optical adhesive sheet is attached to an alkaline glass plate prepared by a float process to obtain a laminate (preparation step). Next, the laminate is subjected to a heating and pressurizing treatment under conditions of 50° C., 0.5 MPa and 15 minutes (heating and pressurizing step). Next, the laminate is left to stand at room temperature for 72 hours (standing step), and then one end of the adhesive sheet piece in the length direction is pulled under first conditions of 25° C., 50% relative humidity, a peeling angle of 180°, and a pulling speed of 300 mm / min to peel the adhesive sheet piece from the alkali glass plate and measure the adhesive strength (measurement step). First ethanol stripping test: The test was the same as the initial room temperature peel test, except for the following: In the standing step, the laminate is stood at 50° C. for 168 hours. After the standing step and before the measuring step, an ethanol supplying step is carried out. In the ethanol supplying step, 10 μL of ethanol is supplied onto the alkaline glass plate of the laminate so that the ethanol contacts one longitudinal end of the adhesive sheet piece at the interface between the alkaline glass plate and the adhesive sheet piece. High temperature and high humidity peeling test: The test was the same as the initial room temperature peel test, except for the following: In the standing step, the laminate is stood at room temperature for 24 hours. After the leaving step and before the measuring step, a high temperature and high humidity treatment step is carried out. In the high-temperature, high-humidity treatment step, the laminate after the standing step is subjected to high-temperature, high-humidity treatment under conditions of 60° C., a relative humidity of 93%, and 15 minutes. In the measuring step, instead of the first condition, a 180° peel test is performed under second conditions of 60° C., relative humidity 93%, a peel angle of 180°, and a tensile speed of 300 mm / min.
2. In the second ethanol peeling test described below, the adhesive strength F 2 and the adhesive strength F a 2 The adhesive force F a 1 The alcohol-peelable optical adhesive sheet according to claim 1, wherein the fluctuation rate of is -50% to 100%. Second Ethanol Stripping Test: The test was the same as the first ethanol peeling test, except that in the standing step, the laminate was stood at room temperature for 72 hours.
3. The alcohol-peelable optical adhesive sheet according to claim 1 , wherein the ethanol peeling duration in the second ethanol peeling test is 20 mm or more.
4. The alcohol-peelable optical adhesive sheet according to claim 1 , which does not contain a surfactant.
Citation Information
Patent Citations
Optical adhesive composition and utilization thereof
JP2020023679A